Coopetition dynamics between giant entrants and incumbents in a new convergent segment: a case in the smartphone industry. Issue 3 (2nd September 2021) - Park, Byung-Jin (Robert); Kim, Dohee
ABSTRACT: This study investigates the dynamic evolution of coopetition between giant entrants from different industries and incumbent leaders, and the role of coopetition in industry leadership battles in a convergent segment. We analyse the case of coopetition between Apple and Samsung in the smartphone industry, taking both a broad perspective and a more focused approach. Our findings suggest that in convergent situations, innovative leaders from other industries are likely to enter newly convergent segments and coopetition between giant entrants and incumbents plays an important role in the industry leadership battles. Also, from the dynamic perspective, the cooperative relationships between giant entrants and incumbents can change to coopetition over time. Thus, the way to value creation will change across the stages of the coopetition and balance is critical for the continuation of a coopetitive relationship.